North Ethiopian Afro‐Alpine Tree Line Dynamics and Forest‐Cover Change Since the Early 20th Century. (13th October 2014) - Jacob, Miro; Frankl, Amaury; Beeckman, Hans; Mesfin, Gebrekidan; Hendrickx, Marijn; Guyassa, Etefa; Nyssen, Jan
Abstract: High‐altitude forests are very important for local livelihood in the vulnerable environment of the densely populated tropical highlands. Humans need the ecosystem services of the forest and directly impact the forest through livestock herding, fire, and wood harvesting. Nevertheless, temperature‐sensitive tree lines in the tropics are scarcely investigated in comparison with higher northern latitudes. In this study, the Erica arborea L. tree line is studied in a tropical mountain in the North Ethiopian highlands: Lib Amba of the Abune Yosef Mountain range (12°04′N, 39°22′E, 3993 m asl). The present tree line and forest cover was recorded by high‐resolution satellite imagery from Google Maps and field data (2010–2013), while historical forest cover was studied from aerial photographs (1965–1982) and repeat photography (1917–2013). The aerial and satellite images were orthorectified and classified in forest/non‐forest binary maps. The binary forest layers were used to detect forest‐cover change and tree line dynamics by image differencing between the three time layers (1965–1982–2010). These maps and a terrestrial photograph indicate two periods of deforestation (1917–1965 and 1982–2013), whereas the forest cover was stable between 1965 and 1982. Deforestation was especially severe (with 63%) between 1982 and 2010, associated with a population increase from 77 to 153 inhabitants per square km. There is significant evidence that the elevation of the E. arborea L. tree line increased from 7 to 15 vertical meters between 1965 and 2010, in an area with decreasing anthropozoogenic pressure. Copyright © 2014 John Wiley & Sons, Ltd.